Exploring the mediating role of trust in food products with Protected Designation of Origin. The case of ´Jamón de Teruel´ - Fandos-Herrera, Carmina (Spanish Journal of Agricultural Research, 2016)
The growing concern about quality in food products has substantially increased the competitiveness of agro-food products that possess quality-system certifications compared to non-certificated products. This research focused on understanding how consumer trust is greater when agro-food products have a Protected Designation of Origin (PDO). In particular, we analyze whether the influence of consumers’ perceived quality of a PDO product has a direct effect on their perceived risk or whether this relationship is mediated by consumer trust, which can help us advance in the study of consumer behavior within the agro-food marketing discipline. Our findings obtained through the comparison of two models, the proposal and another rival, suggest that the initially proposed model present a better fit and explains the relationships better than the rival model, which highlights the essential role of consumer trust in explaining consumers’ perceived risk and their subsequent purchasing behavior. Consequently, managers should pay special attention to consumer trust because trust is the key mediating aspect which allows the incorporation of characteristics highly valued by consumers in food products like origin, tradition and production methods to reduce perceived risk.